The prevalence of nursing mouth caries of preschool children - Dianegianty, Rine; Sasmita, Inne Suherna; Setiawan, Arlette Suzy Puspa Pertiwi (Universitas Padjadjaran, 2014)
Introduction: Mouth Nursing caries is a particular form of dental caries in children and infants. Mouth Nursing Caries occurs in children aged of 2-4 years old and attack the primary maxillary anterior teeth, maxillary and mandibular first primary molar and primary canine mandibular. Nursing caries Mouth happens because of the habit of falling asleep while sucking a bottle containing sweet liquids (baby formula) in a prolonged period. This research aimed to determine the number and the prevalence of preschool children suffering from nursing mouth caries at Cimahi. Methods: The research method was descriptive with survey technique. Samples selected by cluster random sampling technique consisted of 13 kindergartens with 315 preschool children as the total sample. Results: The result shows that 234 or 74 preschool children. 3% have nursing mouth caries and the rest of 81 preschool children or 27.5% do not have nursing mouth caries. Conclusion: This research concludes that the prevalence of Nursing Mouth caries in preschool children at Cimahi in 2012 is74.3% or ¾ of the number of samples Examined.